Evaluated Glomerular Filtration Rate Is Associated With Non-alcoholic Fatty Liver Disease: A 5-Year Longitudinal Cohort Study in Chinese Non-obese People - Cen, Ji; Han, Yong; Liu, Yufei; Hu, Haofei (Frontiers in Nutrition, 2022)
Objective: Evidence regarding the association between evaluated glomerular filtration rate(eGFR) and non-alcoholic fatty liver disease(NAFLD) is still limited. On that account, the purpose of our research is to survey the link of evaluated eGFR on NAFLD. Methods: This study is a retrospective cohort study. Which consecutively and non-selectively collected a total of 16138 non-obese participants in a Chinese hospital from January 2010 to December 2014. We then used the Cox proportional-hazards regression model to explore the relationship between baseline eGFR and NAFLD risk. A Cox proportional hazards regression with cubic spline functions and smooth curve fitting (the cubic spline smoothing) was used to identify the non-linear relationship between eGFR and NAFLD. Additionally, we also performed a series of sensitivity analyses and subgroup analyses. Data had been uploaded to the DATADRYAD website. Results: The mean age of the included individuals was 43.21 ± 14.95 years old, and 8467(52.47%) were male. The mean baseline eGFR was 98.83 ± 22.80 ml/min per 1.73 m2. During a median follow-up time of 35.8 months, 2317(14.36%) people experienced NAFLD. After adjusting covariates, the results showed that eGFR was negatively associated with incident NAFLD (HR=0.983, 95%CI: 0.980, 0.985). There was also a non-linear relationship between eGFR and NAFLD, and the inflection point of eGFR was 103.489 ml/min per 1.73 m2. The effect sizes(HR) on the left and right sides of the inflection point were 0.988 (0.984, 0.991) and 0.971 (0.963, 0.979), respectively. And the sensitive analysis demonstrated the robustness of our results. Subgroup analysis showed that eGFR was more strongly associated with incident NAFLD in diastolic blood pressure(DBP)<90mmHg, fasting plasma glucose(FPG) ≤6.1mmol/L, high-density lipoprotein cholesterol(HDL-c)<1mmol/L, and alanine aminotransferase(ALT) ≥40U/L participants. In contrast, the weaker association was probed in those with DBP≥90mmHg, ALT<40U/L, FPG>6.1mmol/L, and HDL-c≥1mmol/L. Conclusion: This study demonstrates a negative and non-linear association between eGFR and incident NAFLD in the Chinese non-obese population. eGFR is strongly related to NAFLD when eGFR is above 103 ml/min per 1.73 m2. From a therapeutic perspective, it makes sense to maintain eGFR levels within the inflection point to 130ml/min/1.73m2.